."The use of pedagogical innovations in the process of training future technology teachers." - Kucher, S. L. (Problems of Engineer-Pedagogical Education, 2018)
The need for updating approaches and methods of vocational education prompts the use of topical innovative pedagogical technologies. In the process of preparing future technology teachers there are prerequisites for the application of many pedagogical innovations, including information and communication technologies (ICTs), framing approach, case technology, resource-oriented training, and others. The future teacher will master new pedagogical technologies in the process of self-education and self-development, and later this experience will be the basis of professional activity. The close link of educational innovation with the new information dissemination technologies can bring the educational environment closer to the interests of the learner and, thus, increase the efficiency of the educational process. Future educators’ ability to innovate means primarily their desire and opportunity to develop their interests and ideas, to seek their own nontraditional solutions to emerging problems, to perceive and creatively implement existing nonstandard approaches in education